Analisis Legalitas Perparkiran di Kota Gorontalo - Sharul Ramadhan, Aditya (CV. Ulil Albab Corp, 2025)
In accodance Article 27 paragraph (1) of the 1945 Constitution, of republic of Indonesia, it is affirmed that “all citizens shall have equal status before the law and government and shall be obliged torespect the law and government without exception.